The problems of regional development in Montenegro - Radulovic, Janko (Applied Studies in Agribusiness and Commerce, 2013)
Economic development is a continuous, stochastic process considering that development depends on a multitude of historical, political, economic, cultural, ethnic and other factors. In the process of development, each country puts effort into strengthening their manufacturing potential, increasing the competitiveness of their economy by modernizing technology, and raising the level of education, culture etc. Owing to the accentuated actions of these factors, and different social, economic and other circumstances, there has been emerging polarizations in regional development, urbanization and so on. Proof of a country’s level of economic development can be found in various indicators such as capital equipment; the share of manufacturing, agriculture, and foreign trade; the share of the private sector in total ownership; the development of financial institutions and capital markets; the development and stability of the legal system; the development of transport, telecommunication and other infrastructure; the realized standard of living; the development of democracy and human rights protection; preserved environment etc. Economies of developing countries, including Montenegro, are usually characterized by a low capital equipment and low labor productivity, expensive manufacturing and insufficient share of world trade, high import dependence, uncompetitiveness, high unemployment, undeveloped entrepreneurship, and an undeveloped financial institutions. Polarized countries in an economic and development sense, are therefore those which are unevenly developed, and are constantly faced with highly pronounced problems of disparity in regional development and demographic problems. Solving these problems is a long-term process and necessitates. The design of a regional policy that is more efficient than the previous ones, as well, as building a different procedure for fulfilling the adopted regional policies.